Association between tissue hypoxia, perfusion restrictions, and microvascular architecture alterations with lesion-induced impairment of neurovascular coupling - Stadlbauer, Andreas; Kinfe, Thomas Mehari; Zimmermann, Max; Eyüpoglu, Ilker Yasin; Brandner, Nadja; Buchfelder, Michael; Zaiß, Moritz; Dörfler, Arnd; Brandner, Sebastian (Journal of Cerebral Blood Flow and Metabolism, 2020)
Functional magnetic resonance imaging (fMRI) has been mainly utilized for the preoperative localization of eloquent cortical areas. However, lesion-induced impairment of neurovascular coupling (NVC) in the lesion border zone may lead to false-negative fMRI results. The purpose of this study was to determine physiological factors impacting the NVC. Twenty patients suffering from brain lesions were preoperatively examined using multimodal neuroimaging including fMRI, magnetoencephalography (MEG) during language or sensorimotor tasks (depending on lesion location), and a novel physiologic MRI approach for the combined quantification of oxygen metabolism, perfusion state, and microvascular architecture. Congruence of brain activity patterns between fMRI and MEG were found in 13 patients. In contrast, we observed missing fMRI activity in perilesional cortex that demonstrated MEG activity in seven patients, which was interpreted as lesion-induced impairment of NVC. In these brain regions with impaired NVC, physiologic MRI revealed significant brain tissue hypoxia, as well as significantly decreased macro- and microvascular perfusion and microvascular architecture. We demonstrated that perilesional hypoxia with reduced vascular perfusion and architecture is associated with lesion-induced impairment of NVC. Our physiologic MRI approach is a clinically applicable method for preoperative risk assessment for the presence of false-negative fMRI results and may prevent severe postoperative functional deficits.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Blood-oxygen-level-dependent contrast; functional magnetic resonance imaging; hypoxia; magnetoencephalography; neurovascular coupling

Comparative fMRI and MEG localization of cortical sensorimotor function: Bimodal mapping supports motor area reorganization in glioma patients - Zimmermann, Max; Roessler, Karl; Kaltenhaeuser, Martin; Grummich, Peter; Brandner, Nadja; Buchfelder, Michael; Dörfler, Arnd; Kölble, Konrad; Stadlbauer, Andreas (PLoS ONE, 2019)
Introduction
CRIS-Team WoS Importer:2019-03-26

Development of a Non-invasive Assessment of Hypoxia and Neovascularization with Magnetic Resonance Imaging in Benign and Malignant Breast Tumors: Initial Results - Stadlbauer, Andreas; Zimmermann, Max; Bennani-Baiti, Barbara; Helbich, Thomas H.; Baltzer, Pascal; Clauser, Paola; Kapetas, Panagiotis; Bago-Horvath, Zsuzsanna; Pinker, Katja (Molecular Imaging and Biology, 2019)
Purpose: To develop a novel magnetic resonance imaging (MRI) approach for the noninvasive assessment of hypoxia and neovascularization in breast tumors. Procedures: In this IRB-approved prospective study, 20 patients with suspicious breast lesions (BI-RADS 4/5) underwent multiparametric breast MRI including quantitative BOLD (qBOLD) and vascular architecture mapping (VAM). Custom-made in-house MatLab software was used for qBOLD and VAM data postprocessing and calculation of quantitative MRI biomarker maps of oxygen extraction fraction (OEF), metabolic rate of oxygen (MRO2), and mitochondrial oxygen tension (mitoPO2) to measure tissue hypoxia and neovascularization including vascular architecture including microvessel radius (VSI), density (MVD), and type (MTI). Histopathology was used as standard of reference. Appropriate statistics were performed to assess and compare correlations between MRI biomarkers for hypoxia and neovascularization. Results: qBOLD and VAM data with good quality were obtained from all patients with 13 invasive ductal carcinoma (IDC) and 7 benign breast tumors with a lesion diameter of at least 10 mm in all spatial directions. MRI biomarker maps of oxygen metabolism and neovascularization demonstrated intratumoral spatial heterogeneity with a broad range of biomarker values. Bulk tumor neovasculature consisted of draining venous microvasculature with slow flowing blood. High OEF and low mitoPO2 were associated with low MVD and vice versa. The heterogeneous pattern of MRO2 values showed spatial congruence with VSI. IDCs showed significantly higher MRO2 (P = 0.007), lower mitoPO2 (P = 0.021), higher MVD (P = 0.005), and lower (i.e., more pathologic) MTI (P = 0.001) compared with benign breast tumors. These results indicate that IDCs consume more oxygen and are more hypoxic and neovascularized than benign tumors. Conclusions: We developed a novel MRI approach for the noninvasive assessment of hypoxia and neovascularization in benign and malignant breast tumors that can be easily integrated in a diagnostic MRI protocol and provides insight into intratumoral heterogeneity.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Breast cancer; Imaging biomarkers; MRI; Neovascularization; Oxygen metabolism; Tumor hypoxia

Hypoxia and microvascular alterations are early predictors of IDH-mutated anaplastic glioma recurrence - Stadlbauer, Andreas; Oberndorfer, Stefan; Heinz, Gertraud; Zimmermann, Max; Kinfe, Thomas Mehari; Dörfler, Arnd; Buchfelder, Michael; Kremenevski, Natalia; Marhold, Franz (Cancers, 2021)
Anaplastic gliomas (AG) represents aggressive brain tumors that often affect young adults. Although isocitrate-dehydrogenase (IDH) gene mutation has been identified as a more favorable prognostic factor, most IDH-mutated AG patients are confronted with tumor recurrence. Hence, increased knowledge about pathophysiological precursors of AG recurrence is urgently needed in order to develop precise diagnostic monitoring and tailored therapeutic approaches. In this study, 142 physiological magnetic resonance imaging (phyMRI) follow-up examinations in 60 AG patients after standard therapy were evaluated and magnetic resonance imaging (MRI) biomarker maps for microvascular architecture and perfusion, neovascularization activity, oxygen metabolism, and hypoxia calculated. From these 60 patients, 34 patients developed recurrence of the AG, and 26 patients showed no signs for AG recurrence during the study period. The time courses of MRI biomarker changes were analyzed regarding early pathophysiological alterations over a one-year period before radiological AG recurrence or a one-year period of stable disease for patients without recurrence, respectively. We detected intensifying local tissue hypoxia 250 days prior to radiological recurrence which initiated upregulation of neovascularization activity 50 to 70 days later. These changes were associated with a switch from an avascular infiltrative to a vascularized proliferative phenotype of the tumor cells another 30 days later. The dynamic changes of blood perfusion, microvessel density, neovascularization activity, and oxygen metabolism showed a close physiological interplay in the one-year period prior to radiological recurrence of IDH-mutated AG. These findings may path the wave for implementing both new MR-based imaging modalities for routine follow-up monitoring of AG patients after standard therapy and furthermore may support the development of novel, tailored therapy options in recurrent AG.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Anaplastic glioma; Hypoxia; IDH gene mutation; Isocitrate-dehydrogenase; Neovascularization; Physiological MRI; Recurrence; Treatment failure; Vascular cooption

Intraoperative Magnetic Resonance Imaging of Cerebral Oxygen Metabolism During Resection of Brain Lesions - Stadlbauer, Andreas; Merkel, Andreas; Zimmermann, Max; Sommer, Björn; Buchfelder, Michael; Meyer-Bäse, Anke; Rössler, Karl (World Neurosurgery, 2017)
OBJECTIVE: Tissue oxygen tension is an important parameter for brain tissue viability and its noninvasive intraoperative monitoring in the whole brain is of highly clinical relevance. The purpose of this study was the introduction of a multiparametric quantitative blood oxygenation dependent magnetic resonance imaging (MRI) approach for intraoperative examination of oxygen metabolism during the resection of brain lesions. METHODS: Sixteen patients suffering from brain lesions were examined intraoperatively twice (before craniotomy and after gross-total resection) via the quantitative blood oxygenation dependent technique and a 1.5-Tesla MRI scanner, which is installed in an operating room. The MRI protocol included T2*- and T2 mapping and dynamic susceptibility weighted perfusion. Data analysis was performed with a custom-made, in-house MatLab software for calculation of maps of oxygen extraction fraction (OEF) and cerebral metabolic rate of oxygen (CMRO2) as well as of cerebral blood volume and cerebral blood flow. RESULTS: Perilesional edema showed a significant increase in both perfusion (cerebral blood volume +21%, cerebral blood flow +13%) and oxygen metabolism (OEF +32%, CMRO2 +16%) after resection of the lesions. In perilesional nonedematous tissue only, however, oxygen metabolism (OEF +19%, CMRO2 +11%) was significantly increased, but not perfusion. No changes were found in normal brain. Fortunately, no neurovascular adverse events were observed. CONCLUSIONS: This approach for intraoperative examination of oxygen metabolism in the whole brain is a new application of intraoperative MRI additionally to resection control (residual tumor detection) and updating of neuronavigation (brain shift detection). It may help to detect neurovascular adverse events early during surgery.
EVALuna2:102201

Intratumoral heterogeneity of oxygen metabolism and neovascularization uncovers 2 survival-relevant subgroups of IDH1 wild-type glioblastoma - Stadlbauer, Andreas; Zimmermann, Max; Dörfler, Arnd; Oberndorfer, Stefan; Buchfelder, Michael; Coras, Roland; Kitzwoegerer, Melitta; Roessler, Karl (Neuro-Oncology, 2018)
Background: The intratumoral heterogeneity of oxygen metabolism in combination with variable patterns of neovascularization (NV) as well as reprogramming of energy metabolism affects the landscape of tumor microenvironments (TMEs) in glioblastoma. Knowledge of the hypoxic and perivascular niches within the TME is essential for understanding treatment failure. Methods: Fifty-two patients with untreated glioblastoma (isocitrate dehydrogenase 1 wild type [IDH1wt]) were examined with a physiological MRI protocol including a multiparametric quantitative blood oxygen level dependent (qBOLD) approach and vascular architecture mapping (VAM). Imaging biomarker information about oxygen metabolism (mitochondrial oxygen tension) and neovascularization (microvascular density and type) were fused for classification of 6 different TMEs: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation (OxPhos), and glycolysis with/without neovascularization. Association of the different TME volume fractions with progression-free survival (PFS) was assessed using Kaplan-Meier analysis and Cox proportional hazards models. Results: A common spatial structure of TMEs was detected: central necrosis surrounded by tumor hypoxia (with defective and functional neovasculature) and different TMEs with a predominance of OxPhos and glycolysis for energy production, respectively. The percentage of the different TMEs on the total tumor volume uncovered 2 clearly different subtypes of glioblastoma IDH1wt: a glycolytic dominated phenotype with predominantly functional neovasculature and a necrotic/hypoxic dominated phenotype with approximately 50% of defective neovasculature. Patients with a necrotic/hypoxic dominated phenotype showed significantly shorter PFS (P = 0.035). Conclusions: Our non-invasive mapping approach allows for classification of the TME and detection of tumor-supportive niches in glioblastoma which may be helpful for both clinical patient management and research.
EVALuna2:36560

Magnetic resonance imaging biomarkers for clinical routine assessment of microvascular architecture in glioma - Stadlbauer, Andreas; Zimmermann, Max; Heinz, Gertraud; Oberndorfer, Stefan; Dörfler, Arnd; Buchfelder, Michael; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2017)
Knowledge about the topological and structural heterogeneity of the microvasculature is important for diagnosis and monitoring of glioma. A vessel caliber and type-dependent temporal shift in the magnetic resonance imaging signal forms the basis for vascular architecture mapping. This study introduced a clinically feasible approach for assessment of vascular pathologies in gliomas using vascular architecture mapping. Sixty consecutive patients with known or suspected gliomas were examined using vascular architecture mapping as part of the routine magnetic resonance imaging protocol. Maps of microvessel radius and density, which adapted to the vasculature-dependent temporal shift phenomenon, were calculated using a costume-made software tool. Microvessel radius and density were moderately to severely elevated in a heterogeneous, inversely correlated pattern within high-grade gliomas. Additionally, three new imaging biomarkers were introduced: Microvessel type indicator allowing differentiation between supplying arterial and draining venous microvasculature in high-grade gliomas. Vascular-induced bolus peak time shift may presumably be sensitive for early neovascularization in the infiltration zone. Surprisingly, curvature showed significant changes in peritumoral vasogenic edema which correlated with neovascularization in the tumor core of high-grade gliomas. These new magnetic resonance imaging biomarkers give insights into complexity and heterogeneity of vascular changes in glioma; however, histological validations in more well-defined patient populations are required.
EVALuna2:33149

Metabolic tumor microenvironment characterization of contrast enhancing brain tumors using physiologic mri - Stadlbauer, Andreas; Marhold, Franz; Oberndorfer, Stefan; Heinz, Gertraud; Zimmermann, Max; Buchfelder, Michael; Heynold, Elisabeth; Kinfe, Thomas Mehari (Metabolites, 2021)
The tumor microenvironment is a critical regulator of cancer development and progression as well as treatment response and resistance in brain neoplasms. The available techniques for investigation, however, are not well suited for noninvasive in vivo characterization in humans. A total of 120 patients (59 females; 61 males) with newly diagnosed contrast-enhancing brain tumors (64 glioblastoma, 20 brain metastases, 15 primary central nervous system (CNS) lymphomas (PCNSLs), and 21 meningiomas) were examined with a previously established physiological MRI protocol including quantitative blood-oxygen-level-dependent imaging and vascular architecture mapping. Six MRI biomarker maps for oxygen metabolism and neovascularization were fused for classification of five different tumor microenvironments: glycolysis, oxidative phosphorylation (OxPhos), hypoxia with/without neovascularization, and necrosis. Glioblastoma showed the highest metabolic heterogeneity followed by brain metastasis with a glycolysis-to-OxPhos ratio of approximately 2:1 in both tumor entities. In addition, glioblastoma revealed a significant higher percentage of hypoxia (24%) compared to all three other brain tumor entities: brain metastasis (7%; p < 0.001), PCNSL (8%; p = 0.001), and meningioma (8%; p = 0.003). A more aggressive biological brain tumor behavior was associated with a higher percentage of hypoxia and necrosis and a lower percentage of remaining vital tumor tissue and aerobic glycolysis. The proportion of oxidative phosphorylation, however, was rather similar (17–26%) for all four brain tumor entities. Tumor micro-environment (TME) mapping provides insights into neurobiological differences of contrast-enhancing brain tumors and deserves further clinical cancer research attention. Although there is a long roadmap ahead, TME mapping may become useful in order to develop new diagnostic and therapeutic approaches.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Brain tumors; Energy metabolism; Hypoxia; Metabolic imaging; Neovascularization; Physiological MRI; Tumor microenviron-ment

MR Imaging-derived Oxygen Metabolism and Neovascularization Characterization for Grading and IDH Gene Mutation Detection of Gliomas - Stadlbauer, Andreas; Zimmermann, Max; Kitzwoegerer, Melitta; Oberndorfer, Stefan; Roessler, Karl; Dörfler, Arnd; Buchfelder, Michael; Heinz, Gertraud (Radiology, 2017)
Purpose To explore the diagnostic performance of physiological magnetic resonance (MR) imaging of oxygen metabolism and neovascularization activity for grading and characterization of isocitrate dehydrogenase (IDH) gene mutation status of gliomas. Materials and Methods This retrospective study had institutional review board approval; written informed consent was obtained from all patients. Eighty-three patients with histopathologically proven glioma (World Health Organization [WHO] grade II-IV) were examined with quantitative blood oxygen level-dependent imaging and vascular architecture mapping. Biomarker maps of neovascularization activity (microvessel radius, microvessel density, and microvessel type indicator [MTI]) and oxygen metabolism (oxygen extraction fraction [OEF] and cerebral metabolic rate of oxygen [CMRO2]) were calculated. Receiver operating characteristic analysis was used to determine diagnostic performance for grading and detection of IDH gene mutation status. Results Low-grade (WHO grade II) glioma showed areas with increased OEF (+18%, P < .001, n = 20), whereas anaplastic glioma (WHO grade III) and glioblastoma (WHO grade IV) showed decreased OEF when compared with normal brain tissue (-54% [P < .001, n = 21] and -49% [P < .001, n = 41], respectively). This allowed clear differentiation between low- and high-grade glioma (area under the receiver operating characteristic curve [AUC], 1) for the patient cohort. MTI had the highest diagnostic performance (AUC, 0.782) for differentiation between gliomas of grades III and IV among all biomarkers. CMRO2was decreased (P = .037) in low-grade glioma with a mutated IDH gene, and MTI was significantly increased in glioma grade III with IDH mutation (P = .013) when compared with the IDH wild-type counterparts. CMRO2showed the highest diagnostic performance for IDH gene mutation detection in low-grade glioma (AUC, 0.818) and MTI in high-grade glioma (AUC, 0.854) and for all WHO grades (AUC, 0.899) among all biomarkers. Conclusion MR imaging-derived oxygen metabolism and neovascularization characterization may be useful for grading and IDH mutation detection of gliomas and requires only 7 minutes of extra imaging time.©RSNA, 2016 Online supplemental material is available for this article.
EVALuna2:33140

Non-invasive assessment of hypoxia and neovascularization with MRI for identification of aggressive breast cancer - Bennani-Baiti, Barbara; Pinker, Katja; Zimmermann, Max; Helbich, Thomas H.; Baltzer, Pascal A.; Clauser, Paola; Kapetas, Panagiotis; Bago-Horvath, Zsuzsanna; Stadlbauer, Andreas (Cancers, 2020)
The aim of this study was to investigate the potential of magnetic resonance imaging (MRI) for a non-invasive synergistic assessment of tumor microenvironment (TME) hypoxia and induced neovascularization for the identification of aggressive breast cancer. Fifty-three female patients with breast cancer underwent multiparametric breast MRI including quantitative blood-oxygen-level-dependent (qBOLD) imaging for hypoxia and vascular architecture mapping for neovascularization. Quantitative MRI biomarker maps of oxygen extraction fraction (OEF), metabolic rate of oxygen (MRO2), mitochondrial oxygen tension (mitoPO2), microvessel radius (VSI), microvessel density (MVD), and microvessel type indicator (MTI) were calculated. Histopathology was the standard of reference. Histopathological markers (vascular endothelial growth factor receptor 1 (FLT1), podoplanin, hypoxia-inducible factor 1-alpha (HIF-1alpha), carbonic anhydrase 9 (CA IX), vascular endothelial growth factor C (VEGF-C)) were used to confirm imaging biomarker findings. Univariate and multivariate regression analyses were performed to differentiate less aggressive luminal from aggressive non-luminal (HER2-positive, triple negative) malignancies and assess the interplay between hypoxia and neoangiogenesis markers. Aggressive non-luminal cancers (n = 40) presented with significantly higher MRO2 (i.e., oxygen consumption), lower mitoPO2 values (i.e., hypoxia), lower MTI, and higher MVD than less aggressive cancers (n = 13). Data suggest that a model derived from OEF, mitoPO2, and MVD can predict tumor proliferation rate. This novel MRI approach, which can be easily implemented in routine breast MRI exams, aids in the non-invasive identification of aggressive breast cancer.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Breast cancer; Hypoxia; Magnetic resonance imaging; Neovascularization; Tumor aggressiveness

Physiological MRI of microvascular architecture, neovascularization activity, and oxygen metabolism facilitate early recurrence detection in patients with IDH-mutant WHO grade 3 glioma - Stadlbauer, Andreas; Heinz, Gertraud; Oberndorfer, Stefan; Zimmermann, Max; Kinfe, Thomas Mehari; Buchfelder, Michael; Dörfler, Arnd; Kremenevski, Natalia; Marhold, Franz (Neuroradiology, 2021)
Purpose: This study aimed to determine the diagnostic performance of physiological MRI biomarkers including microvascular perfusion and architecture, neovascularization activity, tissue oxygen metabolism, and tension for recurrence detection of IDH-mutant WHO grade 3 glioma. Methods: Sixty patients with IDH-mutant WHO grade 3 glioma who received overall 288 follow-up MRI examinations at 3 Tesla after standard treatment were retrospectively evaluated. A conventional MRI protocol was extended with a physiological MRI approach including vascular architecture mapping and quantitative blood-oxygen-level-dependent imaging which required 7 min extra data acquisition time. Custom-made MATLAB software was used for the calculation of MRI biomarker maps of microvascular perfusion and architecture, neovascularization activity, tissue oxygen metabolism, and tension. Statistical procedures included receiver operating characteristic analysis. Results: Overall, 34 patients showed recurrence of the WHO grade 3 glioma; of these, in 15 patients, recurrence was detected one follow-up examination (averaged 160 days) earlier by physiological MRI data than by conventional MRI. During this time period, the tumor volume increased significantly (P = 0.001) on average 7.4-fold from 1.5 to 11.1 cm3. Quantitative analysis of MRI biomarkers demonstrated microvascular but no macrovascular hyperperfusion in early recurrence. Neovascularization activity (AUC = 0.833), microvascular perfusion (0.682), and oxygen metabolism (0.661) showed higher diagnostic performance for early recurrence detection of WHO grade 3 glioma compared to conventional MRI including cerebral blood volume (0.649). Conclusion: This study demonstrated that the targeted assessment of microvascular features and tissue oxygen tension as an early sign of neovascularization activity provided valuable information for recurrence diagnostic of WHO grade 3 glioma.
CRIS-Team Scopus Importer:2021-06-23
Keywords: Glioma; Humans; Magnetic resonance imaging; Neoplasm recurrence; Neovascularization; Oxygen metabolism; Treatment failure

Physiologic MR imaging of the tumor microenvironment revealed switching of metabolic phenotype upon recurrence of glioblastoma in humans - Stadlbauer, Andreas; Oberndorfer, Stefan; Zimmermann, Max; Renner, Bertold; Buchfelder, Michael; Heinz, Gertraud; Dörfler, Arnd; Kleindienst, Andrea; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2019)
Treating recurrent glioblastoma (GB) is one of the challenges in modern neurooncology. Hypoxia, neovascularization, and energy metabolism are of crucial importance for therapy failure and recurrence. Twenty-one patients with initially untreated GB who developed recurrence were examined with a novel MRI approach for noninvasive visualization of the tumor microenvironment (TME). Imaging biomarker information about oxygen metabolism (mitochondrial oxygen tension) and neovascularization (microvascular density and type) were fused for classification of five different TME compartments: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation, and glycolysis. Volume percentages of these TME compartments were compared between untreated and recurrent GB. At initial diagnosis, all 21 GB showed either the features of a glycolytic dominant phenotype with a high percentage of functional neovasculature (N = 12) or those of a necrotic/hypoxic dominant phenotype with a high percentage of defective tumor neovasculature (N = 9). At recurrence, all 21 GB revealed switching of the initial metabolic phenotype: either from the glycolytic to the necrotic/hypoxic dominant phenotype or vice-versa. A necrotic/hypoxic phenotype at recurrence was associated with a higher rate of multifocality of the recurrent lesions. Our MRI approach may be helpful for a better understanding of treatment-induced metabolic phenotype switching and for future studies developing targeted therapeutic strategies for recurrent GB.
CRIS-Team Scopus Importer:2020-02-21
Keywords: angiogenesis; Glioblastoma; hypoxia; recurrence; treatment failure; tumor microenvironment

Physiologic MR imaging of the tumor microenvironment revealed switching of metabolic phenotype upon recurrence of glioblastoma in humans - Stadlbauer, Andreas; Oberndorfer, Stefan; Zimmermann, Max; Renner, Bertold; Buchfelder, Michael; Heinz, Gertraud; Dörfler, Arnd; Kleindienst, Andrea; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2020)
Treating recurrent glioblastoma (GB) is one of the challenges in modern neurooncology. Hypoxia, neovascularization, and energy metabolism are of crucial importance for therapy failure and recurrence. Twenty-one patients with initially untreated GB who developed recurrence were examined with a novel MRI approach for noninvasive visualization of the tumor microenvironment (TME). Imaging biomarker information about oxygen metabolism (mitochondrial oxygen tension) and neovascularization (microvascular density and type) were fused for classification of five different TME compartments: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation, and glycolysis. Volume percentages of these TME compartments were compared between untreated and recurrent GB. At initial diagnosis, all 21 GB showed either the features of a glycolytic dominant phenotype with a high percentage of functional neovasculature (N = 12) or those of a necrotic/hypoxic dominant phenotype with a high percentage of defective tumor neovasculature (N = 9). At recurrence, all 21 GB revealed switching of the initial metabolic phenotype: either from the glycolytic to the necrotic/hypoxic dominant phenotype or vice-versa. A necrotic/hypoxic phenotype at recurrence was associated with a higher rate of multifocality of the recurrent lesions. Our MRI approach may be helpful for a better understanding of treatment-induced metabolic phenotype switching and for future studies developing targeted therapeutic strategies for recurrent GB.
EVALuna2:212798

PPARδ-mediated mitochondrial rewiring of osteoblasts determines bone mass - Müller, Dorothea; Stoll, Cornelia; Palumbo-Zerr, Katrin; Böhm, Christina; Krishnacoumar, Brenda; Ipseiz, Natacha; Taubmann, Jule; Zimmermann, Max; Böttcher, Martin; Mougiakakos, Dimitrios; Tuckermann, Jan; Djouad, Farida; et al. (Scientific Reports, 2020)
Bone turnover, which is determined by osteoclast-mediated bone resorption and osteoblast-mediated bone formation, represents a highly energy consuming process. The metabolic requirements of osteoblast differentiation and mineralization, both essential for regular bone formation, however, remain incompletely understood. Here we identify the nuclear receptor peroxisome proliferator-activated receptor (PPAR) δ as key regulator of osteoblast metabolism. Induction of PPARδ was essential for the metabolic adaption and increased rate in mitochondrial respiration necessary for the differentiation and mineralization of osteoblasts. Osteoblast-specific deletion of PPARδ in mice, in turn, resulted in an altered energy homeostasis of osteoblasts, impaired mineralization and reduced bone mass. These data show that PPARδ acts as key regulator of osteoblast metabolism and highlight the relevance of cellular metabolic rewiring during osteoblast-mediated bone formation and bone-turnover.
CRIS-Team Scopus Importer:2020-06-02

Predicting Glioblastoma Response to Bevacizumab Through MRI Biomarkers of the Tumor Microenvironment - Stadlbauer, Andreas; Roessler, Karl; Zimmermann, Max; Buchfelder, Michael; Kleindienst, Andrea; Dörfler, Arnd; Heinz, Gertraud; Oberndorfer, Stefan (Molecular Imaging and Biology, 2019)
Purpose: Glioblastoma (GB) is one of the most vascularized of all solid tumors and, therefore, represents an attractive target for antiangiogenic therapies. Many lesions, however, quickly develop escape mechanisms associated with changes in the tumor microenvironment (TME) resulting in rapid treatment failure. To prevent patients from adverse effects of ineffective therapy, there is a strong need to better predict and monitor antiangiogenic treatment response. Procedures: We utilized a novel physiological magnetic resonance imaging (MRI) method combining the visualization of oxygen metabolism and neovascularization for classification of five different TME compartments: necrosis, hypoxia with/without neovascularization, oxidative phosphorylation, and aerobic glycolysis. This approach, termed TME mapping, was used to monitor changes in tumor biology and pathophysiology within the TME in response to bevacizumab treatment in 18 patients with recurrent GB. Results: We detected dramatic changes in the TME by rearrangement of its compartments after the onset of bevacizumab treatment. All patients showed a decrease in active tumor volume and neovascularization as well as an increase in hypoxia and necrosis in the first follow-up after 3 months. We found that recurrent GB with a high percentage of neovascularization and active tumor before bevacizumab onset showed a poor or no treatment response. Conclusions: TME mapping might be useful to develop strategies for patient stratification and response prediction before bevacizumab onset.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Angiogenesis; Antiangiogenic therapy; Bevacizumab; Glioblastoma; Hypoxia; Recurrence; Treatment failure; Treatment monitoring; Tumor microenvironment

Recurrence of glioblastoma is associated with elevated microvascular transit time heterogeneity and increased hypoxia - Stadlbauer, Andreas; Mouridsen, Kim; Dörfler, Arnd; Hansen, Mikkel Bo; Oberndorfer, Stefan; Zimmermann, Max; Buchfelder, Michael; Heinz, Gertraud; Roessler, Karl (Journal of Cerebral Blood Flow and Metabolism, 2018)
Dynamic susceptibility contrast (DSC) perfusion MRI provide information about differences in macro- and microvasculature when executed with gradient-echo (GE; sensitive to macrovasculature) and spin-echo (SE; sensitive to microvasculature) contrast. This study investigated whether there are differences between macro- and microvascular transit time heterogeneity (MVTH and µVTH) and tissue oxygen tension (PO2mit) in newly-diagnosed and recurrent glioblastoma. Fifty-seven patients with glioblastoma (25 newly-diagnosed/32 recurrent) were examined with GE- and SE-DSC perfusion sequences, and a quantitative blood-oxygen-level-dependent (qBOLD) approach. Maps of MVTH, µVTH and coefficient of variation (MCOV and µCOV) were calculated from GE- and SE-DSC data, respectively, using an extended flow-diffusion equation. PO2mit maps were calculated from qBOLD data. Newly-diagnosed and recurrent glioblastoma showed significantly lower ( P ≤ 0.001) µCOV values compared to both normal brain and macrovasculature (MCOV) of the lesions. Recurrent glioblastoma had significantly higher µVTH ( P = 0.014) and µCOV ( P = 0.039) as well as significantly lower PO2mit values ( P = 0.008) compared to newly-diagnosed glioblastoma. The macrovasculature, however, showed no significant differences. Our findings provide evidence of microvascular adaption in the disorganized tumor vasculature for retaining the metabolic demands in stress response of therapeutically-uncontrolled glioblastomas. Thus, µVTH and PO2mit mapping gives insight into the tumor microenvironment (vascular and hypoxic niches) responsible for therapy resistance.
EVALuna2:212789

Refined Functional Magnetic Resonance Imaging and Magnetoencephalography Mapping Reveals Reorganization in Language-Relevant Areas of Lesioned Brains - Zimmermann, Max; Rössler, Karl; Kaltenhäuser, Martin; Grummich, Peter; Yang, Bing; Buchfelder, Michael; Dörfler, Arnd; Kölble, Konrad; Stadlbauer, Andreas (World Neurosurgery, 2019)
BACKGROUND: Neurosurgical decisions regarding interventions close to brain areas with language-related functions remain highly challenging because of the risk of postoperative dysfunction. To minimize these risks, improvements in the preoperative mapping of language-related regions are required, especially as space-occupying lesions often lead to altered cortical topography and language area reorganization. METHODS: The degree of deviation and language area reorganization were investigated in 26 functional magnetic resonance imaging- and magnetoencephalography-dissociable cortical sub-areas displaying language-related activations in each of 18 patients with brain lesions and 3 healthy volunteers (during visual language tasks). RESULTS: Both modalities showed good congruency of the language areas. The mean spatial distance of the centroids and maxima was 9.06 mm and 10.58 mm, respectively, allowing us to define more specific anatomical positions. Postoperatively, language abilities increased in 11% (2 of 18) of the patients, remained unchanged in 83% (15 of 18) of the patients, and decreased in 6% (1 of 18) of the patients, respectively. Signs of language function reorganization detected on both functional magnetic resonance imaging and magnetoencephalography were present in 29% (5 of 17) of the patients. Attenuation of neurovascular coupling was found postoperatively in 17% (3 of 18) of the patients. Monohemispheric language processing cannot be assumed always in patients with brain lesions. CONCLUSIONS: The more detailed subdivision of language-relevant brain areas shown in this study can help to achieve more radical tumor resection without postoperative language deficits.
EVALuna2:212793

Refined Functional Magnetic Resonance Imaging and Magnetoencephalography Mapping Reveals Reorganization in Language-Relevant Areas of Lesioned Brains - Zimmermann, Max; Rössler, Karl; Kaltenhäuser, Martin; Grummich, Peter; Yang, Bing; Buchfelder, Michael; Dörfler, Arnd; Kölble, Konrad; Stadlbauer, Andreas (World Neurosurgery, 2020)
Background: Neurosurgical decisions regarding interventions close to brain areas with language-related functions remain highly challenging because of the risk of postoperative dysfunction. To minimize these risks, improvements in the preoperative mapping of language-related regions are required, especially as space-occupying lesions often lead to altered cortical topography and language area reorganization. Methods: The degree of deviation and language area reorganization were investigated in 26 functional magnetic resonance imaging- and magnetoencephalography-dissociable cortical sub-areas displaying language-related activations in each of 18 patients with brain lesions and 3 healthy volunteers (during visual language tasks). Results: Both modalities showed good congruency of the language areas. The mean spatial distance of the centroids and maxima was 9.06 mm and 10.58 mm, respectively, allowing us to define more specific anatomical positions. Postoperatively, language abilities increased in 11% (2 of 18) of the patients, remained unchanged in 83% (15 of 18) of the patients, and decreased in 6% (1 of 18) of the patients, respectively. Signs of language function reorganization detected on both functional magnetic resonance imaging and magnetoencephalography were present in 29% (5 of 17) of the patients. Attenuation of neurovascular coupling was found postoperatively in 17% (3 of 18) of the patients. Monohemispheric language processing cannot be assumed always in patients with brain lesions. Conclusions: The more detailed subdivision of language-relevant brain areas shown in this study can help to achieve more radical tumor resection without postoperative language deficits.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Brain tumor; Broca; fMRI; Language; MEG; Reorganization; Wernicke

Tissue hypoxia and alterations in microvascular architecture predict glioblastoma recurrence in humans - Stadlbauer, Andreas; Kinfe, Thomas Mehari; Eyüpoglu, Ilker Yasin; Zimmermann, Max; Kitzwoegerer, Melitta; Podar, Klaus; Buchfelder, Michael; Heinz, Gertraud; Oberndorfer, Stefan; Marhold, Franz (Clinical Cancer Research, 2021)
Purpose: Insufficient control of infiltrative glioblastoma (GBM) cells is a major cause of treatment failure and tumor recurrence. Hence, detailed insights into pathophysiologic changes that precede GBM recurrence are needed to develop more precise neuroimaging modalities for tailored diagnostic monitoring and therapeutic approaches. Experimental Design: Overall, 168 physiologic MRI follow-up examinations of 56 patients with GBM who developed recurrence after standard therapy were retrospectively evaluated, that is, two post-standard-therapeutic follow-ups before and one at radiological recurrence. MRI biomarkers for microvascular architecture and perfusion, neovascularization activity, oxygen metabolism, and hypoxia were determined for brain areas that developed in the further course into recurrence and for the recurrent GBM itself. The temporal pattern of biomarker changes was fitted with locally estimated scatterplot smoothing functions and analyzed for pathophysiologic changes preceding radiological GBM recurrence. Results: Our MRI approach demonstrated early pathophysiologic changes prior to radiological GBM recurrence in all patients. Analysis of the time courses revealed a model for the pathophysiology of GBM recurrence: 190 days prior to radiological recurrence, vascular cooption by GBM cells induced vessel regression, detected as decreasing vessel density/perfusion and increasing hypoxia. Seventy days later, neovascularization activity was upregulated, which reincreased vessel density and perfusion. Hypoxia, however, continued to intensify for 30 days and peaked 90 days before radiological recurrence. Conclusions: Hypoxia may represent an early sign for GBM recurrence. This might become useful in the development of new combined diagnostic-therapeutic approaches for tailored clinical management of recurrent GBM. Further preclinical and in-human studies are required for validation and evaluation.
CRIS-Team Scopus Importer:2021-04-09

Vascular architecture mapping for early detection of glioblastoma recurrence - Stadlbauer, Andreas; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Zimmermann, Max; Dörfler, Arnd; Heinz, Gertraud; Oberndorfer, Stefan (Neurosurgical Focus, 2019)
OBJECTIVE: Treatment failure and inevitable tumor recurrence are the main reasons for the poor prognosis of glioblastoma (GB). Gross-total resection at repeat craniotomy for GB recurrence improves patient overall survival but requires early and reliable detection. It is known, however, that even advanced MRI approaches have limited diagnostic performance for distinguishing tumor progression from pseudoprogression. The novel MRI technique of vascular architectural mapping (VAM) provides deeper insight into tumor microvascularity and neovascularization. In this study the authors evaluated the usefulness of VAM for the monitoring of GB patients and quantitatively analyzed the features of neovascularization of early- and progressed-stage GB recurrence. METHODS: In total, a group of 115 GB patients who received overall 374 follow-up MRI examinations after standard treatment were retrospectively evaluated in this study. The clinical routine MRI (cMRI) protocol at 3 Tesla was extended with the authors' experimental VAM approach, requiring 2 minutes of extra time for data acquisition. Custom-made MATLAB software was used for calculation of imaging biomarker maps of macrovascular perfusion from perfusion cMRI as well as of microvascular perfusion and architecture from VAM data. Additionally, cMRI data were analyzed by two board-certified radiologists in consensus. Statistical procedures included receiver operating characteristic (ROC) analysis to determine diagnostic performances for GB recurrence detection. RESULTS: Overall, cMRI showed GB recurrence in 89 patients, and in 28 of these patients recurrence was detected earlier with VAM data, by 1 (20 patients) or 2 (8 patients) follow-up examinations, than with cMRI data. The mean time difference between recurrence detection with VAM and cMRI data was 147 days. During this time period the mean tumor volume increased significantly (p < 0.001) from 9.7 to 26.8 cm3. Quantitative analysis of imaging biomarkers demonstrated microvascular but no macrovascular hyperperfusion in early GB recurrence. Therefore, ROC analysis revealed superior diagnostic performance for VAM compared with cMRI. CONCLUSIONS: This study demonstrated that the targeted assessment of microvascular features using the VAM technique provided valuable information about early neovascularization activity in recurrent GB that is complementary to perfusion cMRI and may be helpful for earlier and more precise monitoring of patients suffering from GB. This VAM approach is compatible with existing cMRI protocols. Prospective clinical trials are necessary to investigate the clinical usefulness and potential benefit of increased overall survival with the use of VAM in patients with recurrent GB.
CRIS-Team Scopus Importer:2019-12-13
Keywords: AUC = area under the ROC curve; CA = contrast agent; CBV = cerebral blood volume; CE = contrast enhanced; cMRI = clinical routine MRI; cNAWM = contralateral normal appearing white brain matter; DSC = dynamic susceptibility contrast; EPI = echo-planar imaging; FN = false negative; FP = false positive; GB = glioblastoma; GE = gradient echo; glioblastoma; MRI; MTI = microvessel type indicator; MVD = microvessel density; neovascularization; OS = overall survival; RANO = Response Assessment in Neuro-Oncology; recurrence; ROC = receiver operating characteristic; ROI = region of interest; SE = spin echo; T1W = T1 weighted; TN = true negative; TP = true positive; VAM = vascular architectural mapping; vascular architecture; VHL = vascular hysteresis loop; VSI = vessel size index; µCBV = microvascular CBV

Vascular Hysteresis Loops and Vascular Architecture Mapping in Patients with Glioblastoma treated with Antiangiogenic Therapy - Stadlbauer, Andreas; Zimmermann, Max; Oberndorfer, Stefan; Dörfler, Arnd; Buchfelder, Michael; Heinz, Gertraud; Roessler, Karl (Scientific Reports, 2017)
In this study, we investigated the variability of vascular hysteresis loop (VHL) shapes and the spatial heterogeneity of neovascularization and microvascular alterations using vascular architecture mapping (VAM) in patients with recurrent glioblastoma during bevacizumab mono-therapy. VAM data were acquired in 13 patients suffering from recurrent glioblastoma prior to and 3 months after bevacizumab treatment onset using a dual contrast agent injections approach as part of routine MRI. Two patients were additionally examined after the first cycle of bevacizumab to check for early treatment response. VHLs were evaluated as biomarker maps of neovascularization activity: microvessel type indicator (MTI) and curvature (Curv) of the VHL-long-axis. Early response to bevacizumab was dominated by reduction of smaller microvasculature (around 10 µm). In the 3-month follow-up, responding tumors additionally showed a reduction in larger microvasculature (>20 µm). VAM biomarker images revealed spatially heterogeneous microvascular alterations during bevacizumab treatment. Responding, non-responding, progressive, and remote-progressive tumor areas were observed. MTI may be useful to predict responding and non-responding tumor regions, and Curv to assess severity of vasogenic edema. Analysis of VHLs in combination with VAM biomarkers may lead to a new perspective on investigating the spatial heterogeneity of neovascularization and microvascular alterations in glioblastoma during antiangiogenic therapy.
EVALuna2:33144